PENINGKATAN PEMASARAN BERBASIS DIGITAL SENI RUPA TOPENG MALANGAN - Nazaruddin Malik; Risky Angga Pramuja; Zainal Arifin (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2020)
Malang Regency has 33 districts. Jabung sub-district is one of the regions in Malang Regency. Jabung village is located in Jabung sub-district, has a population of 9,224 people and an area of 705.78 ha. The number of family heads or families is 2564 with an average family member of 4 people per family. The Jabung Village development index is 0.656 which includes a developing classification. This means that Jabung Village is a village that has village potentials that need to be developed and need real touch and contribution.The conditions that have occurred in Jabug Village for activists in Malang masks are the lack of educational infrastructure and the lack of efforts to preserve the art of Malang masks. This is indicated by the small number of poor mask activists at a young age. Besides, the problem faced by partners in maintaining the Malangan Mask art as an art of ancestral heritage is the inclusion of Westernization culture that has engulfed Indonesia as globalization is expanding resulting in the less desirable local culture. This also had an impact on the Malangan Mask art which was increasingly abandoned by the public. And also the problem of partners is that there are no poor mask educative media to introduce mask characters to visitors, or students who want to learn mask characters.The solution to the problem that occurs in mask craftsmen is by giving lectures about the preservation of the malangan mask art is the absence of science and technology-based educational media for the community (IBM) to preserve and preserve the history of the poor art character. The outcome of the use of Science and Technology for the Community (IBM) is the creation of an e-catalog is a media catalog book in electronic form that makes it easy for everyone to read information through smartphones or other electronic media. Making the malangan mask E-catalog will contain the history and character of the mask as well as souvenir information from the malangan mask art in Jabung village. Key words: Mask Village; Jabung Village; preservatione; science and technology